2023
DOI: 10.1021/acssuschemeng.2c05428
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Phosphate-Incorporated Niobium Carbide as an Effective Electrocatalyst for Ultrasensitive and Selective Monitoring of Monoamine Neurotransmitter

Abstract: The earth-abundant, cost-effective, easier preparation of zinc phosphate eases its diverse implications in recent applications. We have synthesized two-dimensional niobium carbide (NbC)-encapsulated zinc phosphate Zn2P2O7. The physicochemical characteristics were determined, which demonstrate pure crystallinity and good integration of the composite samples. To improve and develop a sustainable environment, the Zn2P2O7/NbC composite will be an efficient material. The detection of pharmaceutical compounds is hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The standard Zn 2p core-level binding energy spectrum is displayed in Figure C. The typical deconvolved Gaussian’s spectrum of the 2p 3/2 and 2p 1/2 are fitted at signals of 1021.1 and 1044.1 eV, respectively, , which confirming ZnO had successfully incorporated.…”
Section: Resultsmentioning
confidence: 83%
“…The standard Zn 2p core-level binding energy spectrum is displayed in Figure C. The typical deconvolved Gaussian’s spectrum of the 2p 3/2 and 2p 1/2 are fitted at signals of 1021.1 and 1044.1 eV, respectively, , which confirming ZnO had successfully incorporated.…”
Section: Resultsmentioning
confidence: 83%
“…To ensure the validity of our proposed sensor system, analytical characteristics such as the linear range of operation on SMZ identification, the threshold of identification, and sensor sensitivities were determined. The following equation (eq 7) calculates the limit of detection (LOD) of the proposed h‐BN/PCN modified GCE towards SMZ [39] boldLboldOboldD=3boldSboldDbolds $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\bf L O D}={\bf \ }{{3{\bf S D}}\over{{\bf s}}}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
“…The following equation (eq 7) calculates the limit of detection (LOD) of the proposed h-BN/PCN modified GCE towards SMZ. [39] LOD ¼ 3SD s (7) Where "s" is the calibration curve's slope and "SD" represents standard deviations of the blank.…”
Section: Sensor Analytical Performancementioning
confidence: 99%
“…This arises due to the ionic strength of the electrolyte, together with the simultaneous interaction occurring at the composite surface. 44 Moreover, the obtained results showed that LMO/f-CNF/GCE has a precise reduction peak current response for each addition of RSN, and that it has strong electrochemical reactivity towards RSN. According to the results, the limit of detection (LOD) was calculated using the following formula: 45 LOD ¼ 3 Â ðstandard deviationÞ slope…”
Section: Dpv Determination Of Rsnmentioning
confidence: 86%